Enhancing productivity, economics and energy efficiency through precision nitrogen and water management in conservation agriculture-based maize (Zea mays) in the Indo-Gangetic Plains - KUMAR, SANDEEP; SINGH, VINOD KUMAR; SHEKHAWAT, KAPILA; KUMAR UPADHYAY, PRAVIN; DWIVEDI, B S; SINGH RATHORE, SANJAY; KUMAR, AVANEESH; YADAV, ARVIND (The Indian Journal of Agricultural Sciences, 2024)
Present study focuses on improving maize productivity, economics, and energy efficiency in the Indo-Gangetic Plains through the integration of CA, precision nitrogen and water management. Maize grain yield significantly differed among treatments, with CA outperforming CT by 13.3%, recording the highest yield with optimal N application (N3) and irrigation at 25% DASM. The CA incurred 23.7% lower cultivation costs (₹30,421/ha) compared to CT. Gross returns and net returns were higher under CA (₹1,16,007/ha and ₹85,586/ha) with a net benefit ratio of 2.78, showcasing its economic viability. Energy efficiency was a crucial aspect considered, with CA proving to be 33.1% more energy-efficient than CT. In different irrigation regimes, CA with W2 treatment exhibited superior energy parameters. The study also highlighted the significance of optimal N scheduling (N3) in achieving higher economic returns (₹97,927/ha) compared to conventional N splits (N1) and its integration. The most effective integration involved combining CA with precision N management (75% basal, GreenSeekerTM-guided top dressing) and irrigation at 25% DASM, resulting in higher grain yield (7.21 t/ ha), gross returns (₹132,497/ha), and impressive energy output (230,831 MJ/ha). In conclusion, CA, especially when combined with optimal irrigation and nitrogen management, not only enhances maize yield and economic returns but also proves to be more energy-efficient, promoting sustainable and resource-efficient agricultural practices. The study recommends this integrated approach for enhancing maize productivity, energy efficiency and economic returns.